The psychologically healthy workplace : building a win-win environment for organizations and employees - Grawitch, Matthew J.; Ballard, David W. (American Psychological Association, 2016)
"The "psychologically healthy" workplace has received much public attention in recent years. But how exactly can a psychologically healthy workplace be created and maintained? What steps can organizations take, without sacrificing the bottom line, to build a culture that optimizes long-term value for employees, management, and shareholders alike? In this book, top scholars focus on the complex interplay between employee and organizational outcomes across five key intervention areas, including: employee involvement--fostering creativity and autonomy of employees, and encouraging involvement in organizational decision-making; work-life balance--providing employees increased flexibility in when, where and how often they work, as well as assistance in navigating life challenges outside of work; employee growth and development--career development and programs to increase competencies; employee recognition--monetary and non-monetary awards in response to significant achievements; and health and safety--promoting healthy behaviors alongside prevention, assessment, and treatment of potential health problems. This work was inspired by the Psychologically Healthy Workplace Program, a public education initiative from APA designed to educate the employer community about the link between employee well-being and organizational performance. With comprehensive examinations of the research literature alongside nuts-and-bolts demonstrations of employee programs and initiatives, this book offers consultants and business leaders alike a blueprint for success"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved).